Literacy Education in the Post-Truth Era: The Pedagogical Potential of Multiliteracies - Parker, Lana; Smith, Kristy (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Current literacy curriculum often reflects an emphasis on traditions of print literacy. This focus is a concern in the post-truth era, as youth engage in diverse meaning-making practices that shape their habits as consumers and producers of information. This in-depth case study investigated the in-class and at-home online behaviors of high school students. We find that even when explicit learning about ‘research’ occurred in class, students are lacking sense-making strategies in their personal online engagements. We also find that curriculum relies on tradition with very little recognition of (multi)literacies as socially constructed and that teachers desire more professional development and guidance about how to engage these literacies more holistically.